15p+p+-19p+20p+-14p-16=-2

Simple and best practice solution for 15p+p+-19p+20p+-14p-16=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15p+p+-19p+20p+-14p-16=-2 equation:


Simplifying
15p + p + -19p + 20p + -14p + -16 = -2

Reorder the terms:
-16 + 15p + p + -19p + 20p + -14p = -2

Combine like terms: 15p + p = 16p
-16 + 16p + -19p + 20p + -14p = -2

Combine like terms: 16p + -19p = -3p
-16 + -3p + 20p + -14p = -2

Combine like terms: -3p + 20p = 17p
-16 + 17p + -14p = -2

Combine like terms: 17p + -14p = 3p
-16 + 3p = -2

Solving
-16 + 3p = -2

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '16' to each side of the equation.
-16 + 16 + 3p = -2 + 16

Combine like terms: -16 + 16 = 0
0 + 3p = -2 + 16
3p = -2 + 16

Combine like terms: -2 + 16 = 14
3p = 14

Divide each side by '3'.
p = 4.666666667

Simplifying
p = 4.666666667

See similar equations:

| 8r+2r-2r-3r-3r=20 | | -5n-(-14n)+-11n+-4n=18 | | 2(x-4)-3(5x-1)=8 | | 7j+6j-12j=17 | | -13h+8h+10h=-20 | | -5x+4x=-20 | | (1-2a)x^2-2ax-1=0 | | 4x^2-29+5x+1=0 | | 9(6x+2)whenx=9 | | (8+i)(7+5i)=0 | | 2*m*n*8= | | 3x+12-5x+10=2x-5x+5 | | q^2-11q+30=0 | | -10x+30=-3x+100 | | 4/x-2=43 | | x^2-8x-15=3x-3 | | x^2+10x+3=7x+1 | | 9x-2=4x+x+4 | | 5/2x=43/4 | | -3x+5=21x | | -122=-6(1-4n)+4 | | 3y-(-1)=4 | | -x-1=3x-2 | | p/4=-1and1/6 | | Y+2x-12=180 | | 1/2(4a-16)=6 | | 3x^2-16x-60=0 | | p4=-1-1/6 | | (1.4)+(-2.3)= | | 7(1-8x)=175 | | x^2+13x+42=6 | | 3x-5=9x-6 |

Equations solver categories